Netnography Study On Covid-19 Vaccination On Dedy Corbuzier's Youtube Podcast - Destriani, Tiara Sella; Murwani, Anis Endang Sri; Indria, Indria (Multidisciplinary Journals, 2024)
This research aims to find out how the netnography study on Deddy Corbuzier's Youtube podcast in the video entitled "Yes I'm not a vaccine!!!". Let's Debate!". This research is a qualitative study using the netnography method. In this study, the authors selected 100 (one hundred) out of ten thousand comments based on comments that received many likes and comments that were most mentioned by netizens. Then make coding which then produces 24 (twenty four) abstractions which are then formed into 5 (five) themes or categories by the author. The theory used in this research is computer mediated communication (CMC). The results showed that after watching this podcast video, many netizens' perspectives changed and became more positive about the Covid-19 vaccination. As for some categories in the results of this study, namely the category of believing or being pro-vaccine, the category of educated audiences, the category of competent sources, the category of dramatization of true stories, the category of hope or vision (future), netizen comments in this category can be used as evaluation material for the government so that it can improve performance for the better in the future. So that later this research can provide an overview of what kind of culture exists on Deddy Corbuzier's youtube podcast video comment page and also that a video on social media can influence and change the culture. The importance of vaccination for the community is to be able to protect themselves from the risk of being exposed to the corona virus and to increase herd immunity in the community.